Pengaruh Morfologi Anionik Flokulan terhadap Performa Koagulasi Nira PG. Krembong PTPN X - Taji, Lulu Sekar; Ardiansyah, Erlangga; Ningrum, Eva Oktavia (Prosiding Seminar Nasional Teknik Kimia "Kejuangan", 2023)
The problem that occurs in Indonesia is the consumption of sugar that is greater than its production which causes the inability of the sugar industry to supply the demand of all consumers. One of the problems that occured is caused by the large number of raw materials that are still imported, including the flocculant used in this case, namely Anionic Polyacrylamide flocculant. Anionic Polyacrylamide (APAM) was first developed using an alkaline hydrolysis process. Until now, APAM manufacturing technology has undergone many developments. However, there are only few research conducted on Anionic poly flocculant (SA-co-A) regarding the influence of polymer properties and the efficiency of its use in the sugar refining process, therefore research was conducted on the influence of Anionic flocculant morphology on the coagulation-flocculation performance of sap at Krembong PTPN X sugar factory to reduce costs in the sugar production process. In this study, poly (SA-co-A) synthesis was carried out as a flocculant to be used in the sugar refining process. The steps used are adding acrylic acid, acrylamide and sodium carbonate which are then added with the NaOH solution. The next step is the synthesis of poly(SA-co-A), the synthesis process is carried out with a nitrogen atmosphere for 3 hours which has previously been added with ammonium persulfate. This study was conducted on the concentration ratio between acrylic acid and acrylamide which uses 40:60, 50:50, 60:40 variables. The resulting flocculants will be tested for flocculant FTIR test, flocculant SEM test, NMR test, settling speed test, mud volume test, pH test, TDS test, turbidity test on sugar’s sap to determine the effect of adding the flocculant. Based on the research that has been done, optimal flocculant performance was obtained, namely on the variable of poly(SA-co-A) 60:40 dose 2.5 ppm, whereas the results are almost equal or even better than commercial flocculant performance. With the removal percentage for the speed of precipitation and the volume of precipitation increases up to 4.5 and 2 times. Then for TDS and turbidity dropped to 14% and 86%.